Users' perceptions of service quality at the Library of Co-operative College, Malaysia / Siti Suhana Adnan - Adnan, Siti Suhana (2009)
This study is an exploratory study which examines the users' perceptions of service quality at the Library of Co-operative College, Malaysia. It attempts to assess the factors that influenced the quality services in CCM Library services, the problems area in library services and the perceived level of successful towards the library services. The survey instrument was a questionnaire adopted from a quality impact survey based on four dimensions in the concrete contexts of library use, according to the factors: "Effect of Service-Organizational," Effect of Service-Personal, " Collection and Access, " and "Library as Ba. " The questionnaire was distributed to a total of 323 full time students at Co-operative College of Malaysia. 181 respondents returned the questionnaire. The SPSS Version 17.0 was used to interpret and analysis the data. Results revealed that the students perceive the quality of library services is good. The Effect of Service - Personal which is focus on library staff is considered most important features of library services that students used. The students' expectation of library that should perform was identified. Based on the results, one has to conclude that the CCM Library a service was achieved a good service and fulfilled the students need.